2006
DOI: 10.1176/appi.ajp.163.3.426
|View full text |Cite
|
Sign up to set email alerts
|

The Schizophrenia Cognition Rating Scale: An Interview-Based Assessment and Its Relationship to Cognition, Real-World Functioning, and Functional Capacity

Abstract: An interview-based measure of cognition that included informant reports was related to cognitive performance as well as real-world functioning. Interview-based measures of cognition, such as the SCoRS, may be valid coprimary measures for clinical trials assessing cognitive change and may also aid clinicians desiring to assess patients' level of cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
247
2
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 349 publications
(262 citation statements)
references
References 19 publications
4
247
2
9
Order By: Relevance
“…For example, the brevity of the UPSA (i.e., 30 minutes) makes it preferable to lengthy batteries assessing multiple cognitive domains. Indeed recent research (Bowie et al, 2006;Keefe et al, 2006) has indicated that the prediction of real-world outcomes is not enhanced by cognitive performance when scores on the UPSA are considered. In addition, unlike assessments of global cognitive functioning (e.g., DRS) healthcare professionals do not need specialized training in order to administer the UPSA.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the brevity of the UPSA (i.e., 30 minutes) makes it preferable to lengthy batteries assessing multiple cognitive domains. Indeed recent research (Bowie et al, 2006;Keefe et al, 2006) has indicated that the prediction of real-world outcomes is not enhanced by cognitive performance when scores on the UPSA are considered. In addition, unlike assessments of global cognitive functioning (e.g., DRS) healthcare professionals do not need specialized training in order to administer the UPSA.…”
Section: Discussionmentioning
confidence: 99%
“…These questions address whether people with schizophrenia have cognitive deficits that impair fundamental aspects of their daily lives. For instance, some of the questions ask whether patients have difficulty remembering names, concentrating well enough to read a newspaper or book, being able to follow group conversations, and handling changes in daily routines (41,42). Interview-based assessments of cognition have historically been unreliable and have demonstrated low correlations with cognitive performance.…”
Section: Interview-based Assessments Of Cognitionmentioning
confidence: 99%
“…A methodology that assesses cognition with interviews of patients and caregivers, such as relatives or caseworkers, appears to have improved reliability and validity. For example, the Schizophrenia Cognition Rating Scale (SCoRS) has been found to have excellent reliability, and substantial correlations with cognitive performance and functional outcomes (41,47). One of the potential weaknesses of this methodology, however, is that reports from patients have been found to have reduced reliability if patients are the only source of information.…”
Section: Interview-based Assessments Of Cognitionmentioning
confidence: 99%
“…Previous studies have shown that patients' self-report of their cognitive functioning tends to be uncorrelated with their performance on cognitive tests (Keefe et al, 2006;van-den-Bosch and Rombouts, 1998). In a study by Keefe and colleagues (Keefe et al, 2006), self-reported cognitive functioning was less strongly related to actual performance than were ratings of an informant or performance on measures of everyday functional skills (i.e., functional capacity).…”
Section: Introductionmentioning
confidence: 96%
“…For example, patients with schizophrenia have notable impairments in cognitive functioning and in the ability to perform everyday functional skills (Bowie and Harvey, 2005;Heaton et al, 1994;Saykin et al, 1991;Twamley et al, 2002). Previous studies have shown that patients' self-report of their cognitive functioning tends to be uncorrelated with their performance on cognitive tests (Keefe et al, 2006;van-den-Bosch and Rombouts, 1998). In a study by Keefe and colleagues (Keefe et al, 2006), self-reported cognitive functioning was less strongly related to actual performance than were ratings of an informant or performance on measures of everyday functional skills (i.e., functional capacity).…”
Section: Introductionmentioning
confidence: 99%